Distinct H2O2-Scavenging System in Yersinia pseudotuberculosis: KatG and AhpC Act Together to Scavenge Endogenous Hydrogen Peroxide - Wan, Fen; Feng, Xue; Yin, Jianhua; Gao, Haichun (Frontiers in Microbiology, 2021)
To colonize in the digestive tract of animals and humans, Yersinia pseudotuberculosis has to deal with reactive oxygen species (ROS) produced by host cells and microbiota. However, an understanding of the ROS-scavenging systems and their regulation in this bacterium remains largely elusive. In this study, by employing genomics and transcriptomics analyses, we identified OxyR as the master transcriptional regulator mediating cellular responses to hydrogen peroxide (H2O2) in Y. pseudotuberculosis. OxyR activates transcription of diverse genes, especially the core of its regulon, including those encoding catalases, peroxidases, thiol reductases and so on. In addition, the data also suggest that sulfur species and manganese may play a particular role in oxidative stress response. Y. pseudotuberculosis is equipped with three H2O2-scavenging systems, catalase/peroxidase KatE, catalase KatG, and AhpC, the peroxidatic component of NADH peroxidase, which typically also contains AhpC’s reducing partner AhpF. While KatE functions as the primary scavenger for high levels of H2O2, AhpC and KatG together are responsible for removing low levels of H2O2. The simultaneous loss of both AhpC and KatG results in activation of OxyR. Moreover, we found that AhpC, unlike its well-characterized Escherichia coli counterpart, has little effect in protecting cells against toxicity of organic peroxides. These findings provide not only insights into how Y. pseudotuberculosis copes with oxidative stress but also a new dimension to the structural and functional diversity of bacterial H2O2-scavenging systems.